Synthesis, characterization and biological activity of new cyclometallated platinum(iv) iodido complexes. Issue 43 (19th October 2017) - Bauer, Emma; Domingo, Xavier; Balcells, Cristina; Polat, Ibrahim H.; Crespo, Margarita; Quirante, Josefina; Badía, Josefa; Baldomà, Laura; Font-Bardia, Mercè; Cascante, Marta
Abstract : Six novel cyclometallated platinum(iv ) iodido complexes are prepared and their cytotoxic activity against a panel of human adenocarcinoma is reported. Abstract : The synthesis of six novel cyclometallated platinum(iv ) iodido complexes is accomplished by intermolecular oxidative addition of methyl iodide (compounds2a–2c ) or iodine (compounds3a–3c ) upon cyclometallated platinum(ii ) compounds [PtX{(CH3 )2 N(CH2 )3 NCH(4-ClC6 H3 )}] (1a–1c : X = Cl, CH3 or I). The X-ray molecular structures of platinum(ii ) compound1c and platinum(iv ) compounds3b and3a′ (an isomer of3a ) are reported. The cytotoxic activity against a panel of human adenocarcinoma cell lines (A-549 lung, MDA-MB-231 and MCF-7 breast, and HCT-116 colon), DNA interaction, topoisomerase I, IIα, and cathepsin B inhibition, and cell cycle arrest, apoptosis and ROS generation of the investigated complexes are presented. Remarkable antiproliferative activity was observed for most of the synthesized cycloplatinated compounds (series1–3 ) in all the selected carcinoma cell lines. The best inhibition was provided for the octahedral platinum(iv ) compounds2a–2c exhibiting a methyl and an iodido axial ligand. Preliminary biological results point to a different mechanism of action for the investigated compounds. Cyclometallated platinum(ii ) compounds1a–1c modify the DNA migration as cisplatin. In contrast, cyclometallated platinum(iv ) compounds2a–2c and3a–3c did not modify the DNA tertiary structure neither in the absence nor in the presence of ascorbic acid, which made them incapable of reducing platinum(iv ) compounds2b and2c in a buffered aqueous medium (pH 7.40) according to 1 H NMR experiments. Remarkable topoisomerase IIα inhibitory activity is reported for platinum(iv ) complexes2b and3a and in addition, for the last one, a moderate cathepsin B inhibition is reported. Cell cycle arrest (decrease in G0/G1 and G2 phases and arrest in the S phase), induction of apoptosis and ROS generation are related to the antiproliferative activity of some representative octahedral cyclometallated platinum(iv ) compounds (2b and2c ).